Experimental study on the interlayer friction and wear mechanism between armor wires of umbilicals. (November 2021) - Yin, Yuanchao; Lu, Qingzhen; Wu, Shanghua; Yang, Zhixun; Yan, Jun; Yue, Qianjin
Abstract: Friction and wear behavior between armor wire layers of umbilical plays an important role in its mechanical properties, in particular its fatigue life. The present paper addresses friction tests to investigate the interlayer sliding friction and wear mechanism of armor wires in an umbilical. A series of friction tests were carried out to study the evolution of coefficient of friction (COF) and wear between armor wire layers. The results show that the COF increases with increasing number of reciprocating sliding cycles in dry friction condition. A dual stable trend was found in the evolution process of interlayer friction and wear of armor wires. A friction model was proposed to describe this trend by dividing the evolution process into three stages: the initial stable stage, the transition stage, and the latter stable stage. The mechanism of the dual stable trend was revealed, which was mainly caused by wear process of nylon fiber tape, and effected by dry/wet wear condition and wear coefficient. The effect of the contact condition, sliding amplitude and number of nylon fiber tape on COF was studied. The COF of the latter stable stage increases with increasing sliding amplitude and number of layers of nylon fiber tape. The finding in this paper provides a valuable approach for a more accurate fatigue life prediction of an umbilical. Highlights: Friction test rig is developed to investigate the interlayer sliding friction and wear mechanism of armor wires in an umbilical. A dual stable trend of COF evolution is discovered and proposed by establishing a theoretical model. The interlayer friction and wear mechanism of the armor wire with the influence of anti-wear nylon fiber tape is revealed by tests. The influence of different parameters on the friction and wear behavior is studied. The dual stable COF evolution trend provides an approach for a more accurate fatigue life prediction of umbilicals.